Improving the soft skills competence of political party cadre through training: a phenomenological approach - Budi Pramono; Ayu Larasati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Soft skills are an important factor considered by many organizations including political parties because they can lead each individual to change behavior for the better. This research is intended to answer the question of how soft skills are applied in their duties and roles as political party cadres, also what problems are encountered by people's representatives who lack competence in soft skills, and what kind of training should be done to overcome the lack of soft skills competence for political party cadres. This is a qualitative research with a phenomenological approach. The term phenomenology is etymologically derived from the Greek. Data collection was carried out by unstructured interviews with 20 informants consisting of 12 political party cadres, 6 community representatives, and 2 academics. The results of this study prove that training related to soft skills for political party cadres is very necessary considering their roles and duties will later become leaders either as representatives of the people, or as leaders in their own regions or at the center. in terms of training materials that still prioritize hard skills over soft skills, in terms of trainers or teaching staff and the methods applied to be more interactive and not one-way.